PEMIKIRAN FUKUZAWA YUKICHI MENGENAI MODERNISASI JEPANG - Intan Anggi Nanda Sari; Prof. Dr. Isjoni, M.Si2 '; Drs. Kamaruddin, M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to describe the condition of Japan during the Tokugawa shogunate, to know what IS the background of the Meiji Restoration, analyzed the thinking of Fukuzawa Yukichi on the modernization of Japan, to know the development of education in Japan, knowing the cultural development in Japan and determine the effect of Fukuzawa Yukichi’s thought against Japan modernization. The method used in this research is descriptive method of historical research, a method that discuss several possibilities to solve actual problems with the way collect data, organize or classify, analyze, and interpret. The study concluded that Fukuzawa Yukichi thinking about modernization in Japan dilator background by the desire to make Japan as a free and independent country in the world. Fukuzawa Yukichi thought about the modernization of education is: a. Datsu A Ron (out of Asia). The most important target is